The Default Mode Network as a Pathological Attractor State: A Hypothesis on Self-Reinforcing Cognitive Loops, Contaminated Baselines, and Implications for Human Health and Consciousness - Khataee, Parviz (Journal of NeuroPhilosophy, 2026)
The Default Mode Network (DMN) has been characterized since its formal description in 2001 as a resting-state network subserving autobiographical memory, social cognition, and prospective thinking. This paper challenges the foundational interpretive assumption of that characterization: that adult human DMN activity constitutes a normal or optimal cognitive baseline. We propose that the DMN, as it operates in virtually all modern adult humans, sustains a chronically hyperactive self-referential attractor state—a persistent loop of involuntary, recursive thought anchored to an emotionally salient virtual self-construct—which we term the Pathological DMN Attractor (PDA). This attractor state is proposed to have emerged adaptively as a continuous social threat-monitoring system, but now operates as an evolutionary mismatch: the natural termination signal—resolution of bounded social threat—is largely absent in modern informational environments, leaving the loop in near-continuous operation. We identify a methodological problem in existing DMN research: the standard adult resting-state baseline used for normative comparison is itself generated by subjects exhibiting the pattern under study, so the reference population and the phenomenon of interest are not clearly separable. We propose that structurally less-contaminated baselines may exist in four populations: pre-linguistic infants, non-human animals with DMN homologs, adults with documented cessation of involuntary self-referential thought, and individuals in acute ego-dissolution states. Comparative analysis across these populations, feasible through reanalysis of existing neuroimaging datasets, would constitute an initial empirical test of the framework. The physiological correlates of chronic PDA activity—autonomic dysregulation, inflammatory load, and sleep architecture disruption—are discussed as downstream effects of what we propose to be a significant, currently overlooked contributing process in a range of stress-related conditions, alongside established mediators such as lifestyle and genetic risk. Testable predictions are proposed.